Mathematics | Study Mode

Join Discuss Share Question Share to WhatsApp
Question 3
A
N250,000.00 
B
N200,000.00 
C
N150,000.00 
D
N100,000.00 
Explanation.
Share Answer N1.00 = $0.075

NX = $15,000

X = \(\frac{1.00 \times 15000}{0.075}\)

= N200,000.00

Correct Option:
B
Join Discuss Share Question Share to WhatsApp
Question 4
A
B
\(\frac{1}{2}\) 
C
-\(\frac{1}{2}\) 
D
-1 
Explanation.
Share Answer \(\frac{27^x \times 3^{1 - x}}{9^{2x}} = 1\)

\(\frac{3^{3x} \times 3^{1 - x}}{3^{2(2 - x)}} = 3^0\)

\(3^{3x} \times 3^{1 - x} \div 3^{4x} = 3^0\)

\(3^{(3x + 1 - x - 4x)} = 3^0\)

\(3^{(1 - 2x)} = 3^0\)

since the bases are equal,

1 - 2x = 0

- 2x = -1

x = \(\frac{1}{2}\)

Correct Option:
B
Join Discuss Share Question Share to WhatsApp
Question 6
A
B
C
12 
D
24 
Explanation.
Share Answer If logx 64 = 3, then 64 = x3

43 = x3

Since the indices are equal,

x = 4

Hence, x log28 = log28x

= log284

= log2(23)4

= log2212

= 1 log2 = 1(1)

= 12

Correct Option:
C
Join Discuss Share Question Share to WhatsApp
Question 7
A
4y\(^\frac{1}{3}\) 
B
4y\(^-3\) 
C
2y\(^\frac{1}{3}\) 
D
2y\(^-3\) 
Explanation.
Share Answer If 2n = y,

then, 2\(^{(2 + \frac{n}{3})}\) = 22 x 2\(^\frac{n}{3}\)

= 4 x (2n)\(^{\frac{1}{3}}\)

But y = 2n, hence

2\(^{(2 + \frac{n}{3})}\) = 4 x y\(^{\frac{1}{3}}\)

= 4y\(^\frac{1}{3}\)

Correct Option:
A
Join Discuss Share Question Share to WhatsApp
Question 8
A
(2a - 3b)(4x + 3y) 
B
(3a + 4b)(2x - 3y) 
C
(3a - 4b)(2x + 3y) 
D
(2a + 3b)(4x -3y) 
Explanation.
Share Answer 6ax - 12by - 9ay + 8bx

= 6ax - 9ay + 8bx - 12by

= 3a(2x - 3y) + 4b(2x - 3y)

= (3a + 4b)(2x - 3y)

Correct Option:
B
Join Discuss Share Question Share to WhatsApp
Question 9
A
4x2 - 13x + 12 = 0 
B
4x2 - 13x - 12 = 0 
C
4x2 + 13x - 12 = 0 
D
4x2 + 13x + 12 = 0 
Explanation.
Share Answer Let x = \(\frac{3}{4}\) or x = -4

i.e. 4x = 3 or x = -4

(4x - 3)(x + 4) = 0

therefore, 4x2 + 13x - 12 = 0

Correct Option:
C
Join Discuss Share Question Share to WhatsApp
Question 10
A
1\(\frac{5}{16}\) 
B
1\(\frac{1}{16}\) 
C
\(\frac{5}{16}\) 
D
- 1\(\frac{37}{48}\) 
Explanation.
Share Answer If m = 4, n = 9, r = 16,

then \(\frac{m}{n}\) - 1\(\frac{7}{9}\) + \(\frac{n}{r}\)

= \(\frac{4}{9}\) - \(\frac{16}{9}\) + \(\frac{9}{16}\)

= \(\frac{64 - 258 + 81}{144}\)

= \(\frac{-111}{144}\)

= - 1\(\frac{37}{48}\)

Correct Option:
D
Next Page
Question Map
Quiz link
Share Mathematics with your friends
Share to WhatsApp Share Quiz CBT mode Study mode copy link